Identification of Compounds and Insecticidal Activity of the Root of Pride of Barbados (Caesalpinia Pulcherrima L) - Oyemwenre Erharuyi; Vincent O. Imieje; Irene O. Oseghale; Abraham E. Ubhenin; A. Biodun Falodun; M. Iqbal Choudhary (Journal of Applied Sciences and Environmental Management, 2017)
Caesalpinia pulcherrima (Caesalpiniaceae) is an ornamental plant with several ethnomedicinal uses. The present study was designed to investigate the brine shrimp cytotoxicity and insecticidal activity of oil obtained from C. pulcherrima root. The powdered root was extracted with methanol and then defatted with petroleum ether (40-60oC) to obtain a viscous oil. The oil was investigated for its brine shrimp cytotoxicity and insecticidal activity in vitro. The chemical constituents were identified by Gas chromatography-Mass spectrometry. The oil showed significant lethal effect against Artemia salina (Brine shrimp) with LC50 of 23.85 μg/mL and mild insecticidal activity against Tribolium castaneum and Callosbruchus analis with percentage mortality of 20% and 40% respectively at 1 mg/cm2. GC-MS analysis identified 37 compounds mainly steroids, terpenoids and fatty acids.